2017
DOI: 10.5797/jnet.oa.2016-0105
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Therapeutic Parent Artery Occlusion without Bypass Surgery for Internal Carotid Artery Aneurysms

Abstract: Objective: When internal carotid artery occlusion is performed for the treatment of an aneurysm, it is important to judge whether or not bypass surgery should be performed for the prevention of complications by the balloon occlusion test (BOT), but there are no clear criteria for the judgment. In this study, we evaluated the long-term results in patients who underwent internal carotid artery occlusion without bypass surgery. Methods:In all, 33 patients with 34 aneurysms who showed no symptoms, a venous phase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The endovascular PAO of the ICA can be performed effectively with detachable balloons and more recently with micro coils [34]. Kuramoto et al reported successful ICA occlusion of 34 aneurysms of 33 patients with periprocedural ischemia in four patients (12%) [35]. A recent study of PAO for treatment of 17 giant CCA aneurysms, revealed complete occlusion in all patients with periprocedural infarct in 5.9% of cases and there was no mortality [36].…”
Section: Proximal Artery Occlusionmentioning
confidence: 99%
“…The endovascular PAO of the ICA can be performed effectively with detachable balloons and more recently with micro coils [34]. Kuramoto et al reported successful ICA occlusion of 34 aneurysms of 33 patients with periprocedural ischemia in four patients (12%) [35]. A recent study of PAO for treatment of 17 giant CCA aneurysms, revealed complete occlusion in all patients with periprocedural infarct in 5.9% of cases and there was no mortality [36].…”
Section: Proximal Artery Occlusionmentioning
confidence: 99%